Potential of aedes breeding site with different types of container at plant nurseries in Klang / Muhammad Afiq Zaki ... [et al.] - Zaki, Muhammad Afiq; Jifri, Intan Syanurin; Mohd Yatim, Siti Rohana; Selamat, Neni Widiasmoro; Ishak, Ruzaina; Zaki, Muhammad Luqman (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Dengue fever which transmitted by the Aedes has been one of the most widespread vector-borne disease. The most important thing in reducing dengue infection cases is by controlling the populations of the Aedes mosquito by destructing Aedes breeding sites. Aedes breeding sites can be determined by conducting a larval survey. Most of the studies conducted were focusing on residential area. However, the mushrooming nursery within housing vicinity has become potential breeding places for aedes since it provides potential artificial and water source to the vector. There were nine plant nurseries have been observed, overall cleanliness and distance from nearest housing area were measured. During the observation, pots, plates, tires, and bucket mostly found in nurseries and may harboring Aedes, hence this study has focused on the container survey and larval collection. Noteworthily, a total of 68 containers were found positive for breeding sites, and most likely the artificial container with larger surface area harboring more than lesser surface area. Adding up to that situation, the relationship between the type of container and likelihood of breeding potential has scored a great observation too. To conclude, aedes breeding places in the nearby nursery might increased potential dengue fever transmission for nearby residences.